Error Performance of Ultrawideband Systems in a Poisson Field of Narrowband Interferers - Win, M.Z.; Pinto, P.C.; Giorgetti, A.; Chiani, M.; Shepp, L.A. (2006 IEEE Ninth International Symposium on Spread Spectrum Techniques and Applications, 2006)
This paper presents a mathematical model for ultrawideband (UWB) communication in the presence of narrowband (NB) interference. In particular, we derive a closed-form expression for the bit error probability of a UWB link, when a Rake receiver is employed and the NB interferers are approximated by sinusoidal tones. The spatial distribution of the NB interferers is accounted for by resorting to a Poisson point process in the two-dimensional plane. We consider a realistic scenario of slowly-moving, asynchronous nodes in a wireless environment subject to path loss, log-normal shadowing, and fast fading (flat Rayleigh fading for the NB nodes; frequency-selective Nakagami-m fading for the UWB link). The proposed model captures all the essential physical parameters that impact UWB-NB interference, but is simple enough to allow a tractable analysis and provide fundamental insights